Peran Religiusitas dalam Meningkatkan Psychological Well Being Santri Putri Program Tahfidz Al-Qur’an di Pondok Pesantren Nurul Islam Jember - Waseso, Putut Nur Falah Ayu; Al Ahsani , Nasirudin (Fakultas Dakwah UIN KHAS Jember, 2023)
All activities in the Islamic boarding school are closely related to the aspect of religiosity, where religiosity is one of several factors influencing the psychological well-being of students. This research aims to examine: 1) How is the religiosity of female students in the Quran memorization program at Pondok Pesantren Nurul Islam in Jember? 2) How is the improvement of psychological well-being among female students in the Quran memorization program at Pondok Pesantren Nurul Islam in Jember? This research uses a qualitative descriptive method with subjects selected based on specific considerations. Data is collected through documentation, interviews, and observations. Data analysis is conducted through condensation, data presentation, conclusion drawing, and verification. Data validity is strengthened through triangulation of techniques and sources. The findings of this study indicate that: 1) Female students in the Quran memorization program at Pondok Pesantren Nurul Islam in Jember have five indicators of religiosity dimensions. However, out of the three informants studied, two still lack in the dimension of religious practice. 2) Female students in the Quran memorization program at Pondok Pesantren Nurul Islam in Jember show good improvement in psychological well-being. They can fulfill six indicators of psychological well-being aspects. However, out of the three informants observed, two of them show a lack of self-acceptance and mastery of the environment aspect.